Experimental life history and biological characteristics of Fasciola gigantica (Digenea: Fasciolidae) - Phalee A. (Korean Journal of Parasitology, 2015)
© 2015, Korean Society for Parasitology and Tropical Medicine. This study was conducted to investigate the life history, morphology, and maturation of larval stages and adult worms of Fasciola gigantica in experimental mice. Lymnaea auricularia rubiginosa was used as the intermediate host, and Oryza sativa was used for encystment of the metacercariae, while Mus musculus was used as the definitive host for maturation study. Fresh eggs from the gall bladder of water buffaloes fully developed into embryonated ones and hatched out at days 11-12 after incubation at about 29ºC. Free-swimming miracidia rapidly penetrated into the snail host, and gradually developed into the next larval stages; sporocyst, redia, and daughter redia with cercariae. Fully-developed cercariae were separated from the redia and shed from the snails on day 39 post-infection (PI). Free-swimming cercariae were immediately allowed to adhere to rice plants, and capsules were constructed to protect metacercariae on rice plants. Juvenile worms were detected in intestines of mice at days 3 and 6 PI, but they were found in the bile duct from day 9 PI. Juvenile and adult flukes were recovered from 16 mice experimentally infected with metacercariae, with the average recovery rate of 35.8%. Sexually mature adult flukes were recovered from day 42 PI. It could be confirmed that experimentally encysted metacercariae could infect and develop to maturity in the experimental host. The present study reports for the first time the complete life history of F. gigantica by an experimental study in Thailand. The obtained information can be used as a guide for prevention, elimination, and treatment of F. gigantica at environment and in other hosts.